1991
DOI: 10.1021/ma00012a032
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption kinetics of block copolymers from a good solvent: a two-stage process

Abstract: The adsorption kinetics and adsorption isotherm of a polystyrene (PS)-poly(ethy1ene oxide) (PEO) diblock copolymer onto a silicon wafer from toluene solution was measured in situ by ellipsometry. Both blocks are in good solvent conditions but the small PEO block is adsorbed while the much larger PS block dangles in solution. Thus, PS-PEO behaves like an end-adsorbed chain. The adsorption kinetics shows two processes on a clearly seperated time scale. In the beginning, the time behavior of the adsorbed amount c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
212
0
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(229 citation statements)
references
References 8 publications
14
212
0
3
Order By: Relevance
“…Figure 1 shows that the kinetics of assembly, based on the adsorbed amount, of PVPb-PS-b-PVP triblock copolymers follows the traditional twostep process observed for the self-assembly of A-B diblock copolymers. 9,14 A fast initial adsorption occurs at early times when there is sufficient free surface area and therefore little interaction among tethered chains. While this regime is often labeled as a "diffusion-limited" regime, at this stage we refer to this regime more generally as the fast initial regime.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows that the kinetics of assembly, based on the adsorbed amount, of PVPb-PS-b-PVP triblock copolymers follows the traditional twostep process observed for the self-assembly of A-B diblock copolymers. 9,14 A fast initial adsorption occurs at early times when there is sufficient free surface area and therefore little interaction among tethered chains. While this regime is often labeled as a "diffusion-limited" regime, at this stage we refer to this regime more generally as the fast initial regime.…”
Section: Resultsmentioning
confidence: 99%
“…These two differences can be explained if we consider that each selfassembled triblock contributes two tethering points (i.e., two equivalent diblocks) to the brush structure. For diblock copolymers, it has been shown that the assembly of the layer, once an overlapped brush is established on the surface, follows an exponential time decay dependence: 14 In eq 8, A deq is the plateau value of the adsorbed amount, A d * and t* are the values of the adsorbed amount and corresponding time after which the exponential model is valid, respectively, and k is the rate constant for this regime. Values of A d * and t* are reported in Table 1 for all copolymers studied.…”
Section: Resultsmentioning
confidence: 99%
“…A linear relationship between and the prevailing concentration c of amphiphile within the adsorption layer is well established [11] …”
Section: Ellipsometry Applied To Ultrathin Filmsmentioning
confidence: 97%
“…19,20 Each layer is usually characterized sequentially regarding independent ellipsometric determinations of thickness and refractive index. 19,20 One should also notice that ellipsometry enables the independent determination of n and d, only if the optical contrast in the system is large enough or if the layer thickness is thick enough. When λ is 633 nm and d >> 30 nm, it is possible to obtain n and d for the uppermost layer independently.…”
Section: Ellipsometrymentioning
confidence: 99%